2014
DOI: 10.1080/15476286.2014.996465
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of human small RNA sequencing data provides insights into expression profiles and miRNA editing

Abstract: MicroRNAs (miRNAs) play key regulatory roles in various biological processes and diseases. A comprehensive analysis of large scale small RNA sequencing data (smRNA-seq) will be very helpful to explore tissue or disease specific miRNA markers and uncover miRNA variants. Here, we systematically analyzed 410 human smRNA-seq datasets, which samples are from 24 tissue/disease/cell lines. We tested the mapping strategies and found that it was necessary to make multiple-round mappings with different mismatch paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 64 publications
2
79
0
Order By: Relevance
“…To ensure the quality of these RNA editing hotspots, we further ruled out the possibility of any unreported SNPs and somatic mutations or cross-mapping (Methods). Among these editing hotspots, 18 (95%) are located at the position 1-8 of mature miRNAs, 12 (63%) have been reported in previous studies (Blow et al 2006;Kawahara et al 2007aKawahara et al ,b, 2008Alon et al 2012;Choudhury et al 2012;Gong et al 2014;Warnefors et al 2014;Saiselet et al 2015;Tomaselli et al 2015;Nishikura 2016), and two editing sites (miR-151a and miR-376a) have been functionally characterized (Kawahara et al 2007a;Choudhury et al 2012). To further characterize these miRNA editing hotspots, we calculated their editing frequency (defined as the fraction of the tumor samples with detectable editing signals), the edited miRNA expression amount (defined as the RPM), and the editing level across cancer types.…”
Section: Systematic Detection Of Rna Editing Hotspots In Mirnas Acrosmentioning
confidence: 71%
See 2 more Smart Citations
“…To ensure the quality of these RNA editing hotspots, we further ruled out the possibility of any unreported SNPs and somatic mutations or cross-mapping (Methods). Among these editing hotspots, 18 (95%) are located at the position 1-8 of mature miRNAs, 12 (63%) have been reported in previous studies (Blow et al 2006;Kawahara et al 2007aKawahara et al ,b, 2008Alon et al 2012;Choudhury et al 2012;Gong et al 2014;Warnefors et al 2014;Saiselet et al 2015;Tomaselli et al 2015;Nishikura 2016), and two editing sites (miR-151a and miR-376a) have been functionally characterized (Kawahara et al 2007a;Choudhury et al 2012). To further characterize these miRNA editing hotspots, we calculated their editing frequency (defined as the fraction of the tumor samples with detectable editing signals), the edited miRNA expression amount (defined as the RPM), and the editing level across cancer types.…”
Section: Systematic Detection Of Rna Editing Hotspots In Mirnas Acrosmentioning
confidence: 71%
“…In addition to protein-coding genes, RNA editing can occur in noncoding genes, such as lncRNAs and microRNAs (miRNAs) (Gong et al 2014(Gong et al , 2017. miRNAs are ∼22-nt small RNAs that function in post-transcriptional gene regulation and participate in various cellular pathways and pathological processes, including cancer (Bartel 2004;Garzon et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, miR-146b-5p is the most highly expressed miRNA in five samples on average and the fourth highest in K562-MVs. It is also highly expressed in The Cancer Genome Atlas acute myelogenous leukemia samples (34) and had a higher expression in acute lymphoblastic leukemia than its controls, according to the HMED database (35).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we studied the miRNA expression profiles based on 9566 and 410 human small RNA sequencing data from TCGA and NCBI SRA, respectively (50). Our analysis revealed that the pool of miRNAs was dominated by a small proportion of abundantly expressed miRNAs and ∼70% of known miRNAs were expressed at low level (RPM < 1) or only expressed in specific tissues.…”
Section: Data Collection and Database Contentmentioning
confidence: 99%